2001
DOI: 10.1097/00006565-200106000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Facial fractures in children

Abstract: Facial fractures were uncommon overall but occurred more frequently in children with major trauma. Plain facial radiographs provided limited additional diagnostic information to careful clinical examination and often fail to detect or clearly define a facial fracture in children. In the correct clinical setting, a facial CT scan allows accurate diagnosis of the injury and can reveal previously unsuspected additional fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
81
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 11 publications
12
81
0
3
Order By: Relevance
“…This finding was similar to previous studies [1,2,7,9,12], however Holland et al [8], Posnik et al [14] and Bamjee et al [15] reported that road traffic accident is the most common cause. Gassner et al [1] reported that majority of accidents occurred during playing (58.2 %) followed by sporting activities (31.8 %), traffic accidents (5 %), assaults (3.9 %).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This finding was similar to previous studies [1,2,7,9,12], however Holland et al [8], Posnik et al [14] and Bamjee et al [15] reported that road traffic accident is the most common cause. Gassner et al [1] reported that majority of accidents occurred during playing (58.2 %) followed by sporting activities (31.8 %), traffic accidents (5 %), assaults (3.9 %).…”
Section: Discussionsupporting
confidence: 92%
“…This was in accordance with Kumarswamy et al [2], Karim et al [9] and Qudah and Bataineh [12]. In contrary mid face fractures were more common in an Australian study by Holland et al [8]. The low incidence of diagnosis of fractures of the mid face is probably because of the lack of modern radiological techniques such as computed tomography.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations